Prevalence, antibiotic resistance and plasmid profiling of Salmonella in catfish (Clarias gariepinus) and tilapia (Tilapia mossambica) obtained from wet markets and ponds in Malaysia - Budiati, T.; Rusul, G.; Wan-Abdullah, W.N.; Arip, Y.M.; Ahmad, R.; Thong, Kwai Lin (Elsevier, 2013)
The objectives of the study were to determine the prevalence, antibiotic resistance and occurrence of plasmids in Salmonella isolated from catfish (Clarias gariepinus) and tilapia (Tilapia mossambica) obtained from wet markets and ponds in Malaysia. A total of 172 samples (32 catfish carcass rinse, 32 catfish intestines, 32 tilapia carcass rinse, 32 tilapia intestines, and 44 water samples) were obtained from nine wet markets and eight ponds that were fed chicken offals, spoiled eggs, and commercial fish feed from 2008 to 2009. Seven Salmonella serovars were isolated from 9/32 catfish (28.1%), 14/32 tilapia (43.8%), and 11/44 (25%) water samples. These include S. Albany, S. Agona, S. Corvallis, S. Stanley, S. Typhimurium, S. Mikawashima and S. Bovis-mobificans. Salmonella isolates were resistant to chloramphenicol (C, 37.2%), clindamycin (Da, 100%), rifampicin (Rd, 90.7%), spectinomycin (Sh, 27.9%), and tetracycline (Te, 67.4%). The multiple antibiotic resistance index of Salmonella isolates ranged from 0.32 to 0.45 for catfish; 0.14 to 0.36 for tilapia; and 0.27 to 0.36 for water. The predominant antimicrobial resistance profiles of Salmonella serovars from catfish, tilapia and water were CDaRdTe (4/13), DaRdSh (4/19), and DaRdTe (6/11), respectively. The plasmids of Salmonella serovars isolated from catfish ranged from 23 to 80 kb; those for tilapia ranged from 6 to 90 kb; that for water ranged from 6 to 70 kb, respectively. The presence of plasmids represents a potential health hazard since plasmids can mediate the transfer of antibiotic resistance genes to other bacteria present in the fish, and aquaculture environment, which can also enter the food chain.